2006
DOI: 10.21273/hortsci.41.5.1165
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation in Somatic Embryogenesis of Rose

Abstract: Fifteen genetically diverse roses were evaluated for the ability to undergo somatic embryogenesis. Over the two media (MS and B5), two sugars (glucose and sucrose), and two explants (filaments and petiole) used, 20 to 30% of the `Tournament of Roses' callus was embryogenic whereas only crystalline callus was produced in cultures of `Baby Love', `Ingrid Bergman', `Perfume Delight', `Prominent', `Sunflare', and 90-202. Cultures of `Tournament of Roses' consistently produced somatic embryos whereas `Baby … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…As many of its cultivars are notably recalcitrant with respect to somatic embryogenesis (Burrell et al 2006;Estabrooks et al 2007), it is of practical value to investigate SERK gene expression as a potential marker of this process in this plant species. Therefore, the aims of our study were to identify SERK gene homologues in a selected rose cultivar and to investigate the expression of these genes in different tissues.…”
Section: Introductionmentioning
confidence: 99%
“…As many of its cultivars are notably recalcitrant with respect to somatic embryogenesis (Burrell et al 2006;Estabrooks et al 2007), it is of practical value to investigate SERK gene expression as a potential marker of this process in this plant species. Therefore, the aims of our study were to identify SERK gene homologues in a selected rose cultivar and to investigate the expression of these genes in different tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Hsia and Korban (1996) found the highest regenerative callus for Carefree Beauty™ was produced on media containing 6% glucose, and Bao et al (2012) reported higher somatic embryo induction and less morphologically abnormal somatic embryos on 3% and 6% glucose than on sucrose for 'Samantha'. However, Burrell et al (2006) reported greater embryogenic callus development on sucrose than glucose for Carefree Beauty™. Occasionally, alternative sugars such as maltose have been used with limited success in 'Frensham', 'Tineke', 'Dr.…”
Section: Resultsmentioning
confidence: 95%
“…The first reports of in vitro regeneration in rose were published in the early 1990s (de Wit et al, 1990;Kunitake et al, 1993;Roberts et al, 1995). This process can be particularly limiting for rose due to the high heterozygosity and recalcitrant nature of many rose cultivars (Burrell et al, 2006). Multiple studies have reported a significant genotype-dependent response for rose regenerative callus production (Hsia and Korban, 1996;Kintzios et al, 1999;Nguyen et al, 2020;Yokoya et al, 1995).…”
mentioning
confidence: 99%
“…A key technique for rose biotechnology has been the induction and regeneration of somatic embryos as reviewed in Roberts et al (1995) as all published transformation protocols make use of regeneration of transgenic plants from somatic embryos. Explant sources for somatic embryogenesis include leaves (de Wit et al, 1990;Rout et al, 1991, Dohm et al, 2001Kim et al, 2004;Estabrooks et al, 2007), stem segments (Rout et al, 1991), immature seeds (Kunitake et al, 1993), petioles and roots (Marchant et al, 1996;Sarasan et al, 2001), filaments and petioles (Burrell et al, 2006), roots (van der Salm et al, 1996a) and protoplast derived callus (Matthews et al, 1991;Schum et al, 2001). The latter reports focus on the isolation of protoplasts from roses, their fusion and the regeneration to intact plants.…”
Section: Rose Biotechnologymentioning
confidence: 99%
“…All reported rose transformation experiments made use of the neomycin phosphotransferase gene (npt II) as a selectable plant transformation marker with varying concentrations of kanamycin for the selection of transgenic tissues. Transformation rates reach a maximum of 3% but are strongly dependent on the genotype due to genotype-dependent regeneration frequencies (Dohm, 2003;Burrell et al, 2006).…”
Section: Genetic Engineeringmentioning
confidence: 99%